Extent of Surgery and the Prognosis of Unilateral Papillary Thyroid Microcarcinoma - Zhao, Hengqiang; Cui, Le (Frontiers in Endocrinology, 2021)
It remains controversial whether patients with papillary thyroid microcarcinoma (PTMC) benefit from total thyroidectomy (TT) or thyroid lobectomy (TL). We aimed to investigate the impact of extent of surgery on the prognosis of patients with unilateral PTMC. Patients were obtained from the Surveillance, Epidemiology, and End Results database from 2004 to 2015. Cancer-specific survival (CSS) and overall survival (OS) were evaluated by Cox regression and Kaplan–Meier curves with propensity score matching. Of 31167 PTMC patients enrolled, 22.2% and 77.8% of which underwent TL and TT, respectively. Patients with TT were more likely to be younger, females, present tumors of multifocality, capsular extension, distant metastasis, and receive radiation compared with those receiving TL. The multivariate Cox regression model showed that TT was not associated with an improved CSS and OS compared with TL with hazard ratio (HR) and 95% confidence interval (CI) of 0.49 (0.23-1.05) and 0.86 (0.72-1.04), respectively. In addition, the Kaplan–Meier curves further confirmed the similar survival between TL and TT after propensity score matching. The subgroup analysis showed that TT was associated with better CSS for patients < 55 years, those with tumors of capsular extension, cervical lymph node metastasis (CLNM), and not receiving radiotherapy with HR 95% CI of 0.17 (0.03-0.88), 0.18 (0.04-0.84), 0.14 (0.05-0.41) and 0.36 (0.14-0.92), respectively. TT also predicted better OS for patients with CLNM and distant metastasis after adjustment. In addition, TT was associated with better CSS than TL for patients with risk factors like CLNM combined with capsular extension, and/or multifocality after matching. In conclusion, TL may be enough for low-risk PTMC patients. TT may improve the prognosis of unilateral PTMC patients with 2 or more risk clinicopathologic factors like CLNM, multifocality, capsular extension and a younger age compared with TL.